Grid-connected current source inverter with instantaneous power control - Nor Amsyar Bin Zainuddin (Nanyang Technological University, 2024)
To keep the grid stable and bring about the intended efficiency with the increased integration of renewable sources of energy, advanced control of the inverters has to be implemented. For the first time, in this study, a grid-connected current source inverter was developed with instantaneous power control, a big breakthrough in the field. The novel power inverter aims to achieve grid-enhanced power quality and reliability through an inverter that can adjust instantly to new load demands in the grid with instantaneous increases or decreases in power. Through theoretical analysis and experimental results, this study developed a new control algorithm that ensures an inverter can instantly control its power output. This was done by designing the perfect inverter circuit, incorporating the appropriate control algorithms and analyzing the performance of the developed inverter under varied load cases to create a grid. The key findings indicate the development of the Current Source Inverter, which can instantly adjust its power output. This is important in enhancing the grid and promoting the excessive integration of variable renewable sources of power. This is important in shifting the current dependent method of power to other stable forms of energy. This report fills the gap in power electronics and integration into the grid. It enables further research into developing inverters to enhance perfect grids and stable and reliable power, hence the significance in the field.